Rice Husk Ash and Fly Ash Effects on the Mechanical Properties of Concrete - Bheel, N.; Jokhio, M. A.; Abbasi, J. A.; Lashari, H. B.; Qureshi, M. I.; Qureshi, A. S. (Engineering, Technology & Applied Science Research, 2020)
Cement production involves high amounts of energy consumption and carbon dioxide emissions. Pakistan is facing a serious energy crisis and cement’s cost is increasing. In addition, landfilling of potential concrete components can lead to environmental degradation. The use of waste as cement replacement not only reduces cement production cost by reducing energy consumption, but it is also environmentally friendly. The purpose of this study is to analyze the characteristics of concrete by partially replacing cement with Rice Husk Ash (RHA) and Fly Ash (FA). This study is mainly focused on the performance of concrete conducting a slump test, and investigating indirect tensile and compressive strength. Cement was replaced with RHA and FA by 5% (2.5% RHA + 2.5% FA), 10% (5% RHA + 5% FA), 15% (7.5% RHA + 7.5% FA) and 20% (10% RHA+10% FA) by weight. Ninety concrete samples were cast with mix proportions of 1:2:4 and 0.55 water/cement ratio. Cube and cylindrical samples were used for measuring compressive and split tensile strength respectively, after 7 and 28 days. The results showed that after 28 days, the 5% RHA+5% FA sample’s compressive strength was enhanced by 16.14% and its indirect tensile strength was improved by 15.20% compared to the conventional sample. Moreover, the sample’s slump value dropped as the content of RHA and FA increased.